Use of a Mixed-Methods Approach to Evaluate the Implementation of Violence and Bullying Prevention Programs in Schools. Issue 6 (July 2021) - Salimi, Nooshin; Karimi-Shahanjarin, Akram; Rezapur-Shahkolai, Forouzan; Hamzeh, Behrooz; Roshanaei, Ghodratollah; Babamiri, Mohammad
School violence and bullying are considered a serious concern worldwide. Evidence shows that applying the Health Promoting Schools (HPS) framework could be effective in reducing school bullying. While there have been significant efforts to evaluate school-based anti-bullying interventions in the world, the implementation process and the effectiveness of this framework in reducing bullying in schools have not been previously evaluated in Iran. This mixed methods study was carried out using simultaneously a cross-sectional (900 students, 104, teachers/school executive staff, and 563 parents) and qualitative study (24 policy makers and teachers/school executive staff) to examine the implementation and effect of counseling and mental health services component of the Iranian Health Promoting School (IHPS) in 2017–2018. Results revealed that there were weaknesses in the implementation of all six elements of anti-bullying programs. A lack of any clean policy toward school violence and bullying, lack of priority set by local decision makers and principals of schools, logistical problems with providing training and supplying counseling resources, limited funding, and presence of competing issues and problems facing the schools were identified as barriers to implement violence and bullying prevention programs in schools. Results also showed that there were no significant differences between non-IHPS and IHPS in students' bullying behaviors ( p = .228) and scores of leadership, the school environment, capacity, partnership, services and support, and evidence ( p > .05). It is essential to revise the content and how to implement anti-bullying programs in schools.